Urinary KIM-1 and AQP-1 in patients with clear renal cell carcinoma: Potential noninvasive biomarkers - Mijušković Mirjana; Stanojević Ivan; Milović Novak; Cerović Snežana; Petrović Dejan; Jovanović Dragan; Aleksić Predrag; Kovačević Božidar; Anđelić Tamara; Terzic Brankica; Đukić Mirjana; Vojvodić Danilo (Vojnosanitetski Pregled)
Background/Aim. Kidney injury molecule-1 (KIM-1) and aquaporin-1 (AQP-1) are potential early urinary biomarkers of clear renal cell carcinoma (cRCC). The aim of this study was to ascertain relationship between the urine concentrations KIM-1 and AQP-1 with tumor size, grade, pT stage and type of operation (radical or partial nephrectomy) in patients with cRCC. Methods. Urinary concentrations of urinary KIM-1 (uKIM-1) and urinary AQP-1 (uAQP-1) were determined by commercially available ELISA kits. The analysis included 40 patients undergoing partial or radical nephrectomy for cRCC and 40 age- and sex-matched healthy adult volunteers. Results. The median preoperative concentrations of KIM-1 in the cRCC group [0.724 ± 1.120 ng/mg urinary creatinine (Ucr)] were significantly greater compared with controls (healthy volunteers) (0.210 ± 0.082 ng/mgUcr) (p = 0.0227). Postoperatively, uKIM-1 concentration decreased significantly to control values (0.177 ± 0.099 ng/mgUcr vs 0.210 ± 0.082 ng/mgUcr, respectively). The size, grade and stage of tumor were correlated positively with preoperative uKIM-1 concentrations. Contrary to these results, concentrations of uAQP-1 in the cRCC group were significantly lower (0.111 ± 0.092 ng/mgUcr) compared with the control group (0.202 ± 0.078 ng/mgUcr) (p = 0.0014). Postoperatively, the concentrations of uAQP-1 increased progressively up to control values, approximately. We find no significant correlation between preoperative uAQP-1 concentrations and tumor size, grade and stage. Conclusion. uKIM-1 was found to be a reliable diagnostic marker of cRCC, based on its significantly increased values before and decreased values after the nephrectomy. [Projekat Ministarstva nauke Republike Srbije, br. III41018]